An aptamer-integrated conductive microneedle biosensor for real-time transdermal cortisol monitoring - Yue Jing, Li; Fan, Yangkai; Zhi Chen, Bo; Li, Dehui; Ting He, Yu; Liang Zhang, Guo; Liang, Ling; Du, Jie; Wang, Yuan; Dong Guo, Xin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•A sensitive, stable, and selective microneedle biosensor was developed for real-time cortisol monitoring in interstitial fluid.•The sensitivity of aptamer-integrated microneedle sensor was boosted by depositing dendritic AuNPs on its surface.•Cortisol detection in healthy volunteers revealed circadian rhythms and a correlation between interstitial fluid and blood levels. Cortisol, known as the ’stress hormone’, plays a crucial role in the regulation of metabolism, the promotion of secondary sex characteristics, and the maintenance of normal biological functions. A conductive microneedle (MN)-based electrochemical biosensor modified with dendritic Au nanoparticles (AuNPs) was developed for real-time monitoring of cortisol levels in interstitial fluid (ISF) to address the current challenges of time-consuming and laborious cortisol detection. The dendritic AuNPs provide signal amplification due to their high surface area and abundance of active sites, and the amine group modification of the cortisol aptamer facilitates its connection to an Au MN electrode with surface-modified dendritic AuNPs. Through parameters optimization and utilization of differential pulse voltammetry (DPV), the MN biosensor exhibits a wide detection range (1–1000 nM) covering normal human cortisol levels. Notably, it demonstrates low computational detection limits of 0.17 nM and 0.22 nM in phosphate buffered saline (PBS) and simulated ISF respectively, along with exceptional stability, selectivity, and repeatability. Furthermore, the successful detection of cortisol in the healthy volunteers’ ISF reveals a significant circadian rhythm and a correlation between cortisol levels in the ISF and blood. Together these findings indicate the promise of aptamer-integrated microneedle biosensors for facilitating simple, sensitive, and disposable cortisol assays.